2015
DOI: 10.1016/j.renene.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Coupled multi-body dynamics and CFD for wind turbine simulation including explicit wind turbulence

Abstract: a b s t r a c tA high fidelity approach for wind turbine aero-elastic simulations including explicit representation of the atmospheric wind turbulence is presented. The approach uses a dynamic overset computational fluid dynamics (CFD) code for the aerodynamics coupled with a multi-body dynamics (MBD) code for the motion responses to the aerodynamic loads. Mann's wind turbulence model was implemented into the CFD code as boundary and initial conditions. The wind turbulence model was validated by comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 39 publications
7
79
0
1
Order By: Relevance
“…Such an approach showed a good agreement with the available simulation results and depicted increased wake diffusion. The methodology plays an important role when a wind turbine operates under complex operational environments, Li et al [123]. There are some studies carried out on flow fans in the literature.…”
Section: Numerical Investigations For Wind Turbine Performance Analysismentioning
confidence: 99%
“…Such an approach showed a good agreement with the available simulation results and depicted increased wake diffusion. The methodology plays an important role when a wind turbine operates under complex operational environments, Li et al [123]. There are some studies carried out on flow fans in the literature.…”
Section: Numerical Investigations For Wind Turbine Performance Analysismentioning
confidence: 99%
“…where (2) where is the generalized coordinate of the k-th body, is the generalized force on k-th body, n is number of bodies, L is the Lagrangian function, T is kinetic energy, U is potential energy.…”
Section: Theory Of Multi-body Dynamicsmentioning
confidence: 99%
“…The conveyor chain in producing line is an enormous system, therefore, complex to analyze with simulation method such as finite element analysis (FEA). The MBD simulation is widely used to model the different body motion for each component of the large system [1], [2]. The constraints which relate with bodies are used to limit motions of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Research results in this area can be found in [16] and [17]. The next area of application for Computational Fluid Dynamics simulations is green building, where the above mentioned research results are used to improve the existing solutions and to develop the new ones, e.g., effective natural ventilation system.…”
Section: Introductionmentioning
confidence: 99%